Comprehensive metabolomics and transcriptomics analyses investigating the regulatory effects of different sources of dietary astaxanthin on the antioxidant and immune functions of commercial-sized rainbow trout - Chen, Li; Wang, Lei; Li, Yaopeng; Wu, Xugan; Long, Xiaowen (Frontiers in Immunology, 2024)
Astaxanthin is an important aquatic feed additive that enhances the antioxidant capacity, and immune function of rainbow trout (Oncorhynchus mykiss); however, very limited information is available on its underlying molecular mechanisms.Haematococcus pluvialis powder, Phaffia rhodozyma powder, and synthetic astaxanthin were added to the commercial feed (no astaxanthin, NA) to prepare three experimental feeds, referred to as the HPA, PRA, and SA groups, respectively, and their actual astaxanthin contents were 31.25, 32.96, and 31.50 mg.kg -1 , respectively. A 16-week feeding trial was conducted on the O. mykiss with an initial body weight of 669.88 ± 36.22 g. Serum and head kidney samples from commercial-sized O. mykiss were collected for metabolomics and transcriptomics analysis, respectively.Metabolomics analysis of the serum revealed a total of 85 differential metabolites between the astaxanthin-supplemented group and the control group. These metabolites were involved in more than 30 metabolic pathways, such as glycerophospholipid metabolism, fatty acid biosynthesis, linoleic acid metabolism, and arginine and proline metabolism. It is speculated that different sources of dietary astaxanthin may regulate antioxidant capacity and immunity mainly by affecting lipid metabolism and amino acid metabolism. Transcriptomic analysis of the head kidney revealed that the differentially expressed genes between the astaxanthin-supplemented group and the control group, such as integrin beta-1 (ITGB1), alpha-2-macroglobulin (A2M), diamine acetyltransferase 1 (SAT1), CCAAT/enhancer-binding protein beta (CEBPB) and DNA damage-inducible protein 45 alpha (GADD45A), which are involved in cell adhesion molecules, the FoxO signaling pathway, phagosomes, and arginine and proline metabolism and play regulatory roles in different stages of the antioxidant and immune response of O. mykiss.